2021
DOI: 10.3390/su13179539
|View full text |Cite
|
Sign up to set email alerts
|

Role of Agricultural Diversification in Improving Resilience to Climate Change: An Empirical Analysis with Gaussian Paradigm

Abstract: Agricultural diversification efforts towards sustainable agriculture generates environmental and economic benefits. Climate change and agricultural production are characterized by a complex cause-effect relationship. In the present study, the primary dataset is collected through an interview-based survey from 410 farmers in 3 districts located in different agro-ecological zones of Punjab, Pakistan. Detailed analysis is conducted by employing the Gaussian treatment effects approach. Results of the study show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Rural areas are extensive and the population is large [1]. How to improve its ability to increase income, improve the diversification of sustainable livelihoods and realize the improvement of the sustainability of farmers' own development capacity is important for social stability and sustainable rural construction [2].…”
Section: Introductionmentioning
confidence: 99%
“…Rural areas are extensive and the population is large [1]. How to improve its ability to increase income, improve the diversification of sustainable livelihoods and realize the improvement of the sustainability of farmers' own development capacity is important for social stability and sustainable rural construction [2].…”
Section: Introductionmentioning
confidence: 99%
“…As such, agroforestry, fishing, and beekeeping were not common agricultural undertakings in the area. Studies, e.g., [33,43], have indicated that a more diverse farming system is more resilient against climate change and environmental shocks. Therefore, it is reasonable to argue that PPT farming systems enhance the climate resilience of smallholder farmers by enabling them to diversify their agricultural activities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that compared resilience across groups of participants such as farming systems, communities, and institutions often rely on a cross-sectional household survey e.g., [31,32]. Due to methodological uncertainties in measuring resilience, the survey should be complemented by participatory approaches such as focus group discussions, which help to capture qualitative insights [32][33][34]. On the other hand, studies that focused on analyzing changes in resilience over time have used panel data, e.g., [35,36].…”
Section: Data Sources and Samplingmentioning
confidence: 99%
“…In this context, the transition to the production of environmentally friendly products is considered optimal. Research by Kiani et al (2021) in 3 areas located in different agri-environmental zones of Punjab (Pakistan) show that the losses of farmers who have adopted agricultural diversification to mitigate the effects of climate change have been lower. An average of $635 per year was lost by those who adopted diversification, while the farmers who did not adopt had lost their farm income by an average of $772 (Kiani et al, 2021).…”
Section: Authors' Declarations and Essential Ethical Compliancesmentioning
confidence: 99%